Semiotic Analysis Of The Index In Revealing RomanticismOn Poetry By Joko Pinurbo - Padli Alfareza; Samsiarni Samsiarni; Emil Septia (Journal of Linguistica, 2024)
This research aims to examine the concept of romanticism as understood by Russell Noyes in the poetry of Joko Pinurbo, utilizing Charles Sanders Peirce's semiotic theory with a focus on the index as a key object. The study is conducted using a qualitative descriptive method, analyzing ten data points extracted from five of Joko Pinurbo's poems: "Kosmetik," "Salam Sembuh," "Kisah Natal," "Ramadan di Rantau," and "Ngabuburit." The research methods employed include close reading and note-taking to identify and interpret the presence of index signs within these poems. Through the analysis of these index signs, the study identifies three distinct schools of romanticism as they manifest in the works of Joko Pinurbo. The focus of the research is on interpreting the indexes to uncover the underlying romantic elements within the poetry. This involves a detailed examination of how the indexical signs contribute to the overall theme and emotional resonance of the poems, aligning with the broader genre of romanticism. The findings provide insights into the unique way Joko Pinurbo's poetry embodies romantic themes, as seen through the lens of semiotic analysis, thereby